2015
DOI: 10.3389/fncel.2015.00018
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and acute brain injury

Abstract: Inflammation is the key host-defense response to infection and injury, yet also a major contributor to a diverse range of diseases, both peripheral and central in origin. Brain injury as a result of stroke or trauma is a leading cause of death and disability worldwide, yet there are no effective treatments, resulting in enormous social and economic costs. Increasing evidence, both preclinical and clinical, highlights inflammation as an important factor in stroke, both in determining outcome and as a contributo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
124
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 239 publications
0
124
0
4
Order By: Relevance
“…Stroke causes upregulation of the IL-1 receptor and its ligands in animal models [41], with expression of IL-1α seen in microglia within 4 h postreperfusion [42]. Furthermore, exogenous administration of IL-1β exacerbates ischaemic damage in rodent models, with the absence of IL-1α or IL-1β in knockout mice ameliorating damage [43]. A recent meta-analysis showed that IL1Ra administration was associated with a 38.2 % reduction in mean infarct volume across 16 published preclinical studies [44].…”
Section: Interleukin-1mentioning
confidence: 99%
“…Stroke causes upregulation of the IL-1 receptor and its ligands in animal models [41], with expression of IL-1α seen in microglia within 4 h postreperfusion [42]. Furthermore, exogenous administration of IL-1β exacerbates ischaemic damage in rodent models, with the absence of IL-1α or IL-1β in knockout mice ameliorating damage [43]. A recent meta-analysis showed that IL1Ra administration was associated with a 38.2 % reduction in mean infarct volume across 16 published preclinical studies [44].…”
Section: Interleukin-1mentioning
confidence: 99%
“…IL-1␤ is the most implicated pro-inflammatory cytokine in various pathologies of the central nervous system, including TBI (6,7). Interleukin-1 (IL-1) inhibition has beneficial effects as demonstrated in experimental models of brain damage (6). IL-1␤ induces BBB breakdown in rat brain endothelial cells and also increases human brain microvascular endothelial cell permeability (8).…”
mentioning
confidence: 99%
“…IL-1␤ is the most implicated pro-inflammatory cytokine in various pathologies of the central nervous system, including TBI (6,7). Interleukin-1 (IL-1) inhibition has beneficial effects as demonstrated in experimental models of brain damage (6).…”
mentioning
confidence: 99%
“…Insults to the brain are known to cause a myriad of downstream effects, including the release of cytokines by astrocytes and resultant reactive gliosis [7] [8]. Cytokines are thought to be a major mediator of reactive gliosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β is a pro-inflammatory cytokine that exerts an important role in developing brains as a maintenance and growth-promoting factor [10] [11] and in migration of cortical neurons [12]. IL-1β is secreted by activated astroglia and microglia in brain, where it exerts a diverse range of activities on immune function and coordination of many aspects of the acute phase response to trauma and infection [8] [10]. Inflammation is the key hostdefense response to infection and injury but is also thought to be a major contributor to a diverse range of diseases.…”
Section: Introductionmentioning
confidence: 99%